Characterization of genomic clones specifying rabbit alpha- and beta-ventricular myosin heavy chains. - Friedman, D J (1984)
We have isolated gene sequences coding for the alpha- and beta-myosin heavy chains (HC) of rabbit ventricular muscle. A rabbit genomic library was screened with previously characterized cDNA clones specifying part of the light meromyosin and the entire subfragment 2 portion of alpha- and beta-myosin HCs, as well as with a clone containing the 3' nontranslated sequences of the alpha-myosin HC mRNA. Seven strongly hybridizing clones were analyzed in detail. One genomic clone encoded all of the 3' nontranslated sequences of an alpha-cDNA clone and, therefore, contained the 3' end of the alpha-myosin HC gene. Electron microscopic heteroduplex analysis and DNA sequence analysis showed that this clone overlapped a second genomic clone providing more than 25 kilobase pairs of the alpha-myosin HC gene. The exons within this region corresponded to approximately equal to 85% of the mRNA and were separated by at least 28 introns. A clone for the beta-myosin HC gene was also identified by Southern blot hybridization, by heteroduplex mapping, and by comparing the DNA sequence of a subfragment 2 exon to sequences of the alpha- and beta-cDNA clones. The introns of the alpha- and beta-myosin HC genes were in the same position but showed marked variation in length. These results conclusively showed that the alpha- and beta-myosin HCs are products of separate genes.